A combination of a common splice site mutation and frameshift mutation in the COL7A1 gene: absence of functional collagen VII in keratinocytes and skin - Hammami Hauasli, Nadja; Ulrike Kalinke, D.; Schumann, Hauke; Kalinke, Ulrich; Pontz, Bertram F.; Anton-Lamprecht, Ingrun; Pulkkinen, Leena; Zimmermann, Mirjam; Uitto, Jouni; Bruckner-Tuderman, Leena (The journal of investigative dermatology, 1997)
We describe a patient with severe generalized dystrophic epidermolysis bullosa (EBD) and a novel combination of compound heterozygous mutations in the COL7A1 gene. The maternal mutation was an A-to-G transition (425-A → G) at position −2 of the donor splice site within exon 3 that causes aberrant splicing of two abnormal transcripts. One includes intron 3, and one excludes both exon 3 and intron 3. Both splice variants contained a premature termination of the translation. The paternal mutation is a 25-bp deletion in exon 20 (2638de125) that leads to a frameshift and a premature termination codon 133bp downstream from the site of deletion. This combination of mutations allowed expression of collagen VII mRNA. Immunofluorescence staining of the patient's skin and cultured keratinocytes with domain-specific collagen VII antibodies, however, demonstrated markedly reduced levels of α1(VII) polypeptides, and no stable collagen VII protein could be extracted from the patient's cells. Electron microscopy showed severely hypoplastic fibrils below the lamina densa, without evidence of normal anchoring fibrils. The clinically unaffected parents were heterozygous for the mutations, suggesting that both COL7A1 gene defects were recessively inherited disease-causing mutations that are “silent” in heterozygous carriers but in combination can severely interfere with the dermal-epidermal adhesion and lead to severe EBD.
Elektronische Reproduktion der Druck-Ausgabe 8. Dezember 2015
Gesehen am 23.10.2023